Feasibility of salt pads to improve fat suppression in low-field MRI systems. Issue 4 (November 2022) - Sakoda, K.; Oura, R.; Baba, S.
Abstract: Introduction: Fat-suppressed images are essential in clinical practice but are often affected by magnetic field inhomogeneity, resulting in poor image quality. We hypothesized that salt (99% sodium chloride [NaCl]) could be used as a magnetic field uniformity assist pad and verified whether salt pads improve magnetic field uniformity and the fat suppression effect in low-field magnetic resonance imaging (MRI) systems. Methods: We conducted a small clinical study where coronal 2D fast spin-echo T2-weighted MRI with fat suppression was performed. The subjects were 10 healthy volunteers (six men and four women) with no surgical history, with a mean age of 20.5 years (range, 20–30 years). In the clinical study, we performed physical and visual evaluation by imaging a subject's knee with and without salt pads. Results: The results of the clinical study indicated that the use of salt pads improved the magnetic field uniformity, thus increasing the fat suppression effect. Conclusions: Salt pads improved the homogeneity of the magnetic field and the fat suppression effect in low-field MRI systems. Implications for practice: The use of salt pads in low-field MRI systems could provide more accurate fat suppression images.